Computational Thinking Development in children both neurotypical and with Intellectual Disabilities by the Game “Pensar e Vestir” - Soppa Geremias, Matheus; Cerigueli Dutra, Taynara; Maschio, Eleandro; Gasparini, Isabela (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
With a focus on problem resolution, Computational Thinking (CT) can assist in developing cognitive abilities. A way to work with CT is using educational digital games (EDG), a ludic tool that stimulates the students’ learning. Still, adjustments are needed so that students with Intellectual Disabilities (ID) can use these games. Based on this scenario, we presented a Bachelor’s final paper that envisioned the creation of an EDG, aiming to contribute to the learning of the target audience, based on the promotion of the development of CT. Called “Pensar e Vestir”, the game uses the four pillars of CT by addressing choosing and wearing clothes. For that, the development counted with a multidisciplinary group – stakeholders and specialists from the areas of Computer Science, Education, Specialized Educational Assistance, and ID – and followed the Simple Interaction Design lifecycle model, with the definition of requirements, designing alternatives, prototyping, and evaluation. As a result, this EDG has two phases and eight situations each: time to sleep, the school in the heat, school in the cold, costume, park, tour, teacher, and market. The game was evaluated by specialists, Computing students, and one neurotypical child, we also intend to make a large evaluation with the target audience. As an outcome, the interaction design process with different stakeholders and specialists provides different insights and improvements to the game. Also, the game is accessible to neurotypical and with ID students.